Morphological and molecular features of stain fungi infecting rubberwood (Hevea brasiliensis) - Dodi Nandika; Arinana Arinana; Ali Bin Abithalib Salman; Julia Yonipi Putri (Society for Indonesian Biodiversity, 2021)
Abstract. Nandika D, Arinana, Salman ABA, Putri JY. 2021. Morphological and molecular features of stain fungi infecting rubberwood (Hevea brasiliensis). Biodiversitas 22: 5408-5416. In the southeast Asia region, particularly Indonesia, Thailand, and Malaysia, rubberwood (Hevea brasiliensis Muell. Arg.) has been widely used as a raw material in various industries particularly furniture manufacturing. However, rubberwood is highly susceptible to fungal attack due to its lack of heartwood formation. A laboratory study was conducted to investigate the morphological and molecular features of stain fungi infecting rubberwood. A total of five isolates of stain fungi belonging to three genera were identified based on internal transcribed spacer (ITS) and morphological features. All isolates belong to Order Eurotiales with each genus being Paecilomyces, Aspergillus, and Penicillium. The highest growth rate on wood samples was shown by Aspergillus chevalieri section Aspergillus and Paecilomyces maximus or P. formosus with values of 86.57% and 86.22%, respectively. All of the stain fungi genera caused varied level of discoloration on wood samples with dark grayish and very dark grayish as the more frequent color found. Quantitatively, the highest discoloration was shown by A. chevalieri section Aspergillus (?E = 27.60) and P. maximus or P. formosus (?E = 16.69). These species can be considered as newly stain fungi recorded infecting rubberwood in Indonesia. In addition, discoloration caused by these two stain fungi was the worst.